2017
DOI: 10.1080/09168451.2016.1240606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, oxygen radical absorbance capacity, and tyrosinase inhibitory activity of glycosides of resveratrol, pterostilbene, and pinostilbene

Abstract: The stilbene compound resveratrol was glycosylated to give its 4'-O-β-D-glucoside as the major product in addition to its 3-O-β-D-glucoside by a plant glucosyltransferase from Phytolacca americana expressed in recombinant Escherichia coli. This enzyme transformed pterostilbene to its 4'-O-β-D-glucoside, and converted pinostilbene to its 4'-O-β-D-glucoside as a major product and its 3-O-β-D-glucoside as a minor product. An analysis of antioxidant capacity showed that the above stilbene glycosides had lower oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Several derivatives of the parent resveratrol have been described as potential depigmenting agents, with oxyresveratrol (IC50 = 1.7 μM) [55] and particularly dihydrooxyresveratrol (IC50 = 0.3 μM) [55] among the most active compounds. Recently, glycosylation has been reported to improve the tyrosinase inhibitory activities of both resveratrol and its methylated analogues pterostilbene and pinostilbene [60]. Another major class of mushroom tyrosinase inhibitors is represented by hydroxystilbenes ( Figure 5).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
See 1 more Smart Citation
“…Several derivatives of the parent resveratrol have been described as potential depigmenting agents, with oxyresveratrol (IC50 = 1.7 μM) [55] and particularly dihydrooxyresveratrol (IC50 = 0.3 μM) [55] among the most active compounds. Recently, glycosylation has been reported to improve the tyrosinase inhibitory activities of both resveratrol and its methylated analogues pterostilbene and pinostilbene [60]. Another major class of mushroom tyrosinase inhibitors is represented by hydroxystilbenes ( Figure 5).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Several derivatives of the parent resveratrol have been described as potential depigmenting agents, with oxyresveratrol (IC 50 = 1.7 µM) [55] and particularly dihydrooxyresveratrol (IC 50 = 0.3 µM) [55] among the most active compounds. Recently, glycosylation has been reported to improve the tyrosinase inhibitory activities of both resveratrol and its methylated analogues pterostilbene and pinostilbene [60]. Moving to simple phenols, significant inhibition activity has been described for 4-hydroxybenzyl alcohol (IC50 = 6 μM) [61] and isoeugenol (IC50 = 33.3 μM) [62], which would appear more efficient than resorcinol [55] or rhododendrol [63] themselves.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Another study revealed that pinostilbene displayed in vitro cytotoxicity with IC 50 value of 78.13 μM against NCI‐H187 cell line (Lertnitikul et al, ). Pinostilbene was shown to possess high antioxidant capacity displaying a value of 5.01 Trolox equivalents/μM in an oxygen radical absorbance capacity assay (Uesugi et al, ). The antioxidant capacity could have been contributed to the cytotoxicity of pinostilbene, reported in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Three glycosyltransferases namely Pa GT1, Pa GT2, and Pa GT3 have been isolated from the callus tissues of P. americana (11). Among the three Pa GTs, Pa GT3 can glycosylate a wide variety of substrates, such as capsaicin, flavonoids, hydroxyflavones, and stilbenoids (11, 22, 23). Although Pa GT2 can also regioselectively glucosylate stilbenoids and flavonoids, the detail has not been much explored.…”
Section: Introductionmentioning
confidence: 99%